Makam Papan Tinggi Sebuah Simbol Sosio Religius Islam: Kajian Historis Masyarakat Barus Tapanuli Tengah Sumatera - Ellya Roza; Annisa Rahma Luthfi; Dhea Reza Nirmala; Ditya Natasya Hasibuan; Winda Permata Astuti; Sukma Erni (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The Papan Tinggi Tomb is an old historical site located in Panangahan Village, North Barus, in the midst of a predominantly non-Muslim community. The existence of this site builds the assumption that a Muslim civilization was built in the early years of Islam entering and developing in the archipelago. This study uses a simple qualitative method to find a more comprehensive picture of early Islamic civilization in the land of Sumatra. Data were obtained by conducting participant observation at the tomb location which is on a hill with almost 1000 steps, interviews with tomb guards, visitors who come and reinforced by the results of previous studies. The results of the study explain that this tomb is the final resting place of Sheikh Mahmud al-Muftazam, a Sufi figure who helped spread Islam and Sufism in the Barus area which then spread throughout the archipelago. In addition to the tomb of Sheikh Mahmud, there are other tombs that are thought to be his students in the same tomb complex. Because of its role and services, this tomb is considered sacred and is now one of the religious tourism destinations. Although the main information about the area has not been explored well, the Zero Point Monument for the Spread of Islam in the Archipelago which was inaugurated by the government has at least opened the eyes of the world and the local community to the importance and strength of a civilization that once existed on the shores of Barus Beach.